2000
DOI: 10.1088/0953-8984/12/33/316
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamic dielectric behaviour of ferroelectric [NH2(CH3)2]3Sb2Br9(DMABA)

Abstract: The crystal structure of DMABA has been determined at 293 and 180 K. It crystallizes in the monoclinic P21/c space group. The structure was refined to R1 = 0.0466 for 1269 independent reflections at 293 K and R1 = 0.038 for 1728 reflections at 180 K. DMABA is isomorphous with the chlorine analogue, DMACA. Its anionic sublattice forms corrugated two-dimensional layers in the bc plane. There are two crystallographically independent, disordered dimethylammonium cations in the crystal structure. One of them occupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…A special attention deserve haloantimonates(III) and halobismuthate(III) because many compounds described by the R 3 M 2 X 9 (2D dimensionality) and R 5 M 2 X 11 composition were found to exhibit the ferroelectric properties [9][10][11]. The later type of crystals is characterized by a discrete bioctahedral unit (0D).…”
Section: Introductionmentioning
confidence: 99%
“…A special attention deserve haloantimonates(III) and halobismuthate(III) because many compounds described by the R 3 M 2 X 9 (2D dimensionality) and R 5 M 2 X 11 composition were found to exhibit the ferroelectric properties [9][10][11]. The later type of crystals is characterized by a discrete bioctahedral unit (0D).…”
Section: Introductionmentioning
confidence: 99%
“…It has turned out that the ferroelectric properties had some tendency to appear in the two-dimensional (2D) anionic sublayers encountered in the R 3 M 2 X 9 -type compounds. On the other hand, several synthesized ferroelectrics crystallize in R 5 M 2 X 11 composition, where the discrete bioctahedral units, M 2 X 5À 11 , constitute the anionic sublattice [6][7][8][9][10][11]. The role of the cations, their size and symmetry, is not fully recognized yet.…”
Section: Introductionmentioning
confidence: 99%
“…The hexabromobismuthate(III) anion, as well as two of the three crystallographically unrelated allylammonium cations are ordered. The N1-C2-C3-C4 and the N11-C12-C13ϪC14 torsion angles of the ordered cations are equal to 106.1 (9) and -112. 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies have shown that the ferroelectric properties have some tendency to appear in the 2D anionic substructures encountered in R 3 M 2 X 9 -type connections. [6][7][8][9] So far, several synthesised ferroelectrics were found to crystallise with a R 5 M 2 X 11 composition in which the anionic network con-(IV↔V) at 146/144 K. The ferroelastic domain structure was observed over one intermediate phase (III) below 215 K. The electric properties of ABB have been measured over a wide temperature range (105-310 K). Low frequency relaxation processes with dielectric increments Δε 1 ≈ 0.9 and Δε 2 ≈ 0.05 were observed within phases II and V, respectively.…”
Section: Introductionmentioning
confidence: 99%